Predictors of Placebo Response in Pharmacological Clinical Trials of Negative Symptoms in Schizophrenia: A Meta-regression Analysis. (19th January 2018) - Fraguas, David; Díaz-Caneja, Covadonga M; Pina-Camacho, Laura; Umbricht, Daniel; Arango, Celso
Abstract: We conducted a meta-regression analysis of all double-blind, randomized, placebo-controlled clinical trials (DBRCTs) reporting effects of drug and placebo on negative symptoms in people with stable schizophrenia and predominant or prominent negative symptoms to assess predictors of placebo response in these individuals. We used Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines for systematic reviews and meta-analyses to conduct a systematic literature search to identify DBRCTs assessing treatment efficacy on negative symptoms, as primary outcome, in patients with stable schizophrenia and predominant or prominent negative symptoms. We used Cohen's d, with 95% CIs, as the effect size measure for placebo response, based on negative symptom change scores from baseline to endpoint (range 4 to 24 wk) in the placebo-treated group. We included 18 DBRCTs from 17 publications, assessing the effect of 13 drugs vs placebo on negative symptoms and comprising 998 patients, in the meta-regression analyses. Overall, drugs showed greater efficacy than placebo in reducing negative symptoms, with small effect size (Cohen's d : 0.208, P = .020). Placebo response was significant ( P < .001) and clinically relevant (Cohen's d : 2.909), but there was significant heterogeneity and high risk of publication bias. Multivariable meta-regression analyses showed that larger numbers of arms in the trial, larger numbers of study sites and industry sponsorship were significant moderators of placebo response in this population. Our results suggest that some clinical trial design and operational factors affect the level of placebo response in such studies, thus highlighting the need for designs better suited to assess these outcomes.